2005
DOI: 10.1016/j.joca.2005.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and clinically important differences for the WOMAC and SF-36 after hip joint replacement

Abstract: These values indicate expected gains after THR. However, the MCID and MDC values must be viewed cautiously due to the uncertainty of these estimators and should not be considered as absolute thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
161
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(196 citation statements)
references
References 25 publications
20
161
4
1
Order By: Relevance
“…Other studies have previously explored the issue of whether patients responded to THR (4,16,27,28). An early US study by MacWilliam et al identified predictors of outcome in 1,500 patients receiving THR (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have previously explored the issue of whether patients responded to THR (4,16,27,28). An early US study by MacWilliam et al identified predictors of outcome in 1,500 patients receiving THR (27).…”
Section: Discussionmentioning
confidence: 99%
“…One of the difficulties in trying to decide whether an individual has or has not responded to THR is that disease severity at the time of surgery varies enormously (15), and that there are floor and ceiling effects in the patientreported outcome measures used to assess severity (16). Ceiling effects occur when a large number of patients have the maximum score (i.e., most severe disease; these patients have the greatest potential to improve following surgery), whereas floor effects occur when a high percentage of patients have the minimum score (e.g., no pain or functional limitations).…”
Section: Introductionmentioning
confidence: 99%
“…It also is possible that waiting only 6 months to assess the impact of a THA may have introduced bias. Although some studies report that improvement is seen at 6 months [8,9,12,25], some suggest a longer followup period is needed [20]. Third, the WOMAC provides valuable information and is considered the correct instrument for evaluating changes in studies such as ours [15,26].…”
Section: Discussionmentioning
confidence: 90%
“…When working with the WOMAC and other instruments, showing clinically meaningful changes, not just statistically significant changes, is crucial. Therefore, we used the MCID of the WOMAC [25]. However, even the MCID must be used carefully and not as an absolute measure, as there are several practical problems in estimating that parameter [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation